Privação auditiva unilateral de início tardio: avaliação comportamental e eletrofisiológica - Wieselberg, Margarita Bernal [UNIFESP] (2010)
Introduction: There are numerous and proven clinical advantages in fitting bilateral hearing aids in cases of bilateral hearing loss: localization of sound, clarity, redundancy, binaural and stereo hearing addition effect. However, it still remains a significant number of unilateral fittings in cases of bilateral hearing loss, with long periods without proper auditory stimulation in the unaided ear. This indicates to be the basis of a phenomenon called "Late-onset auditory deprivation”. Objective: To characterize the auditory performance of individuals with bilaterally symmetrical sensorineural hearing loss fitted with unilateral hearing aid, through behavioral and electrophysiological tests. Methods: Thirty five adults (males and females) participated in the study. All subjects with bilateral symmetric sensorineural hearing loss acquired in adulthood, distributed into three groups: 1) Study Group: 15 unilaterally aided subjects; 2) Unaided Comparison Group: ten unaided subjects; 3) Bilaterally Aided Comparison Group: ten bilaterally aided subjects. All participants underwent the same evaluation protocol constituted of interviews, behavioral tests under headphones (pure-tone audiogram; suprathreshold speech-recognition score test; duration pattern test – DPT; Pediatric Speech Intelligibility Test – PSI; Sentences in Noise Test - LSP), electrophysiological testing (late auditory evoked potential - P300) and behavioral test in sound field (Sentences in Noise Test - LSP). All tests were performed without hearing aids. A descriptive analysis of all variables considered in the study was performed. The level of significance was p<0.05. Results: In the Unilateral Aided Study Group, the analysis of the results between the formal unaided and aided ear showed no differences in interaural performance for the following tests: suprathreshold speech-recognition score test, DPT, PSI and LSP. On the other hand, in the electrophysiological assessment, the P300 waveform revealed a significant (p<0.05) higher latency in the unaided ear compared to the aided ear of the Study Group. Amplitude of the P300 waveform revealed no difference between aided and unaided ears in this group. In both Bilateral Aided and Unaided Comparison Groups the differences were non-significant for the interaural performance (right ear vs. left ear) in all the tests applied. The evaluation of the Sentences in Noise Test (LSP) in sound field revealed a significant performance difference when comparing the Unilateral Aided Study Group to the Unaided Comparison Group and, showing yet, a trend to significance when compared to the Bilateral Aided Comparison Group. Conclusion: Subjects with bilateral hearing loss who are unilaterally aided showed a longer latency of the P300 potential at the unaided ear when compared to the aided ear. In the behavioral assessment under earphones, there were no interaural differences at the suprathreshold speech-recognition score test, DPT, PSI or LSP. In the behavioral assessment in sound field they showed a poorer performance in the Sentences in Noise Test (LSP).